2001
DOI: 10.1093/ajcn/74.4.426
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weekly administration of pegylated recombinant human OB protein on appetite profile and energy metabolism in obese men

Abstract: Background: Results of leptin administration in mice, rats, and humans provide a rationale for therapeutic augmentation of circulating leptin (OB protein) concentrations in obese humans; this may reduce food intake, increase metabolic rate, and lower body mass. Objective: We assessed the effects of weekly subcutaneous pegylated polyethylene glycol (PEG)-OB protein administration on appetite and energy metabolism in obese men. Design: We performed a randomized, double-blind, placebocontrolled trial in 30 obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 35 publications
2
79
0
Order By: Relevance
“…Furthermore, their study took place in a laboratory setting; participants lived in a metabolic Leptin and appetite responses M Mars et al unit at the time of the study, while the subjects in the present study were free living. Westerterp-Plantenga et al 22 and others found lower hunger and appetite levels in obese male subjects receiving pegylated leptin intravenously than in BMI-and agematched subjects receiving a placebo. 23 Like in the present study, they only observed an effect on appetite while measured in a fasting state.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Furthermore, their study took place in a laboratory setting; participants lived in a metabolic Leptin and appetite responses M Mars et al unit at the time of the study, while the subjects in the present study were free living. Westerterp-Plantenga et al 22 and others found lower hunger and appetite levels in obese male subjects receiving pegylated leptin intravenously than in BMI-and agematched subjects receiving a placebo. 23 Like in the present study, they only observed an effect on appetite while measured in a fasting state.…”
Section: Discussionmentioning
confidence: 89%
“…11 Up till now, several studies have investigated the association between leptin levels and appetite or food intake in humans, either during conditions of energy balance [14][15][16][17][18][19][20] or energy imbalance. [21][22][23] Especially, the latter studies found evidence for the hypothesis that leptin is involved in the restoration of negative energy balances via appetite. Westerterp-Plantenga et al 22 found a decrease in appetite ratings by administration of exogenous leptin during energy restriction.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…16 In a previous study with administration of 20 mg/week pegylated recombinant human leptin, we found that appetite in the postabsorptive state was reduced, but no difference in body mass loss or body composition compared to placebo treatment was demonstrated. 17 In that study, hunger (factor 3, Three-Factor Eating Questionnaire (TFEQ); Stunkard and Messick 18 ) was reduced in the PEG-OB group and cognitive restraint (factor 1, TFEQ) was increased in the placebo group during treatment.…”
Section: Introductionmentioning
confidence: 93%